Factors Associated with Opioid Dose Increases: A Chart Review of Patients' First Year on Long-Term Opioids. Issue 5 (28th July 2016) - Bautista, Christopher A.; Iosif, Ana-Maria; Wilsey, Barth L.; Melnikow, Joy A.; Crichlow, Althea; Henry, Stephen G.
Abstract : Objective. To examine encounter-level factors associated with opioid dose increases during patients' first year on opioid therapy for chronic pain. Design. Case-control study analyzing all opioid prescriptions for patients with chronic pain during their first year after opioid initiation. Cases were patients who experienced an overall dose escalation of ≥ 30 mg morphine equivalents over the 1-year period; controls did not experience overall dose escalation. Main measures were encounter type, opioid dose change, documented prescribing rationale, documentation of guideline-concordant opioid-prescribing practices. Two coders reviewed all encounters associated with opioid prescriptions. Analysis of factors associated with dose increases and provider documentation of prescribing rationale was conducted using multiple logistic regression. Results. There were 674 encounters coded for 66 patients (22 cases, 44 controls). Fifty-three percent of opioid prescriptions were associated with telephone encounters; 13% were associated with e-mail encounters. No prescribing rationale was documented for 43% of all opioid prescriptions and 25% of dose increases. Likelihood of dose increase and documentation of prescribing rationale did not significantly differ for cases versus controls. Compared with face-to-face encounters, dose increases were significantly less likely for telephone (OR 0.18, 95% CI 0.11–0.28) and e-mail (OR 0.23, 95% CI 0.12–0.47) encounters; documentation of prescribing rationale was significantly more likely for e-mail (OR 5.06, 95% CI 1.87–13.72) and less likely for telephone (OR 0.30, 95% CI 0.18–0.51) encounters. Conclusion. Most opioid prescriptions were written without face-to-face encounters. One quarter of dose increases contained no documented prescribing rationale. Documented encounter-level factors were not significantly associated with overall opioid dose escalation.